HUBUNGAN ANTARA GAYA MENGAJAR GURU DENGAN INTERAKSI SOSIAL TERHADAP PRESTASI BELAJAR PELAJARAN MATEMATIKA DI SMK PGRI 1 SURAKARTA - Ningsih, Nur Wigati (Universitas Sahid Surakarta, 2015)
This research purpose to knowing the relation between teacher styles teach with students social interaction and also teacher styles teach with achievement learn and social interaction with students achievement learn in accepting mathematics lesson.Measuring instrument used by teacher style teaches scale, social interaction scale and also use the achievement learn mathematics value. Population is student of PGRI I Vocational High School of Surakarta summed apply sample of counted 60 students, is obtained through the technique of purposive random sampling. The dataanalyze method used analyze Product Moment from Pearson technique with constructively SPSS for Windows Release 21.0.Result of data analysis indicate that there is positive relation which significant between teacher style teach with the achievement learn, shown by a correlation value (r) equal to 0,468; p = 0,002 (p<0,05) meaning progressively style goodness teach the teacher of hence good progressively also achievement learn the student, so also on the contrary bad progressively style teach the teacher of hence bad progressively also achievement learn the student. Analyze hereinafter interaction social with the achievement learn the student obtained a correlation coefficient value (r) 0,524; p = 0,001 (p<0,05), its meaning progressively social interaction goodness learn hence good progressively also achievement learn the student, so also on the contrary bad progressively social interaction learn hence bad progressively also achievement learn student.Key word: Achievement Learn, Teacher Style Teach, Students